1994
DOI: 10.1071/rd9940349
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive vaccine assessment based on a murine ZP3 mini-autoantigen

Abstract: A summary is presented of published and some unpublished observations from studies on the immunological response of mice to a 13-mer peptide of the murine ovarian zona pellucida glycoprotein ZP3. The findings have the following implications for the design of immunocontraceptive vaccines. To be reversible, a ZP3 vaccine must not contain pathogenic T cell epitopes of ZP3, but contraception without autoimmune oophoritis may be feasible. The immune response to the ZP3 mini-autoantigen is highly variable among inbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Simultaneously, it may also lead to activation of ZP3-specific T cells that in turn could cause autoimmune ovarian disease. It has been demonstrated that T cells per se (probably Thl phenotype), not autoantibody, initiate the disease in a mouse model [27,32]. For a contraceptive vaccine using a conventional immunization strategy, it will be extremely important to avoid inclusion of the harmful T-cell epitope with the useful ZP3 B-cell epitope [15].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, it may also lead to activation of ZP3-specific T cells that in turn could cause autoimmune ovarian disease. It has been demonstrated that T cells per se (probably Thl phenotype), not autoantibody, initiate the disease in a mouse model [27,32]. For a contraceptive vaccine using a conventional immunization strategy, it will be extremely important to avoid inclusion of the harmful T-cell epitope with the useful ZP3 B-cell epitope [15].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to determine whether C-terminal processing occurs in the possum and to examine the function of this non-conserved region in marsupial fertilisation. Peptide vaccines based on this epitope have been investigated in mice and primates (Tung et al, 1994;Bagavant et al, 1997) and are currently being examined for their ability to elicit an immune response and block fertilisation in the brushtail possum. Figure 5 Analysis of ZP3 expression in tissues of adult brushtail possum (Trichosurus vulpecula).…”
Section: Discussionmentioning
confidence: 99%
“…Immunocontraceptives, regardless of their physiological targets, most commonly the zona pellucida of the ovum (Tung et al 1994;Kaul et al 1996) or the gonadotropin-releasing hormone of the hypothalamus (GnRH; Hunter and Byers 1996), and contraceptives delivered in biologically modified organisms (Robinson et al 1997) present another potential genetic concern. Because the immunocompetence of differing species (Frank et al 2005), differing strains (Haddad et al 1994) and even individual animals in a single population (Lyda et al 2005) is often markedly different, immunocontraception has the potential to skew population genetics.…”
Section: Geneticsmentioning
confidence: 99%